2020
DOI: 10.13189/ujar.2020.080402
|View full text |Cite
|
Sign up to set email alerts
|

Sesame Seed Yield and Growth Traits Response to Different Row Spacing in Semi-Arid Regions

Abstract: Plant density is one of the most important factors influencing the physiological, morphological characteristics, and yield of sesame. Sesame is an important oilseed and cash crop production in Sudan. The effects of different rows spacing on the growth attributes, yield and yield compound on three sesame seeds varieties were investigated at rainfall conditions in semi-arid regions. Two field experiments were conducted in 2014-2015 and 2015-2016. Three varieties were planted at four rows spacing [5(control), 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The reason could be attributed to the difference in the genetic characteristics of the cultivars and their speed of response to environmental conditions, which was reflected in the variation in the number of branches per plant. The results are in line with findings of previous studies [15,16] which pointed out that the number of branches is depended on genetic diversity among sesame cultivars.…”
Section: Number Of Branches (Branch Plant -1 )supporting
confidence: 93%
“…The reason could be attributed to the difference in the genetic characteristics of the cultivars and their speed of response to environmental conditions, which was reflected in the variation in the number of branches per plant. The results are in line with findings of previous studies [15,16] which pointed out that the number of branches is depended on genetic diversity among sesame cultivars.…”
Section: Number Of Branches (Branch Plant -1 )supporting
confidence: 93%
“…Also, it has been demonstrated that plant density in the farm is one of the most important factors that influences sesame yield [63]. A study by Ali et al [64] in Gedaref showed that planting sesame at 5 cm between rows can increase its yield by 210.18 kg ha −1 . For sorghum, our results showed that the climatic variables were responsible for 70% of the variation in its yield.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that there is prospect of using those phenotypic characters as selection criteria in breeding programs for enhanced sesame yield. Ali et al (2020) also reported that taller plants with the higher number of capsules are favorable for seed yield improvement in sesame. In our study, genotypes BARI til-4, GM-11, CW-1, GM-10, GM-9 and GM-8 had the tallest plants accompanied with higher capsules plant -1 .…”
Section: Discussionmentioning
confidence: 95%